Threat Modeling for a Secured Software Development (International Journal of Advanced Research in Computer Science, 2017)
Security system evaluation is an important and essential activity which could be conducted at different stages in the life cycle of a software development. Understanding the threats to the software is critical step in creating a secure product. Recent researches have demonstrated that threat modeling can provide a basis for building flawless software that can withstand any potential attack. Threat modeling plays an important role in developing secure software which describes a threat subjected on to a system and the harm that could arise on vulnerabilities. The vulnerabilities or loop holes in the securities arise as flaws in requirement specification or designing or results in incomplete implementation or throw out several bugs in testing stage. Increase in the complexity of the software, possibly introduces more design errors which leads to security vulnerabilities and increases security attacks. Hence, it is insisted that the security issues must no more be considered as non-functional requirements and isolated to single phase alone in Software Development Life Cycle (SDLC). These security issues can be well identified using the threat modeling followed in almost all the phases in SDLC.Â Keywords: Software Development Life Cycle (SDLC), Threat Modeling, Threat, Requirement, Design, Development, Testing.